Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1002/pssa.2210350103
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide doped with gallium

Abstract: Silicon carbide (SiC) films doped with gallium are obtained during the process of epitaxial growth using the sublimation variant “sandwich method” or diffusion. It is determined by neutron activation analysis that the gallium solubility in SiC in the temperature range 1800 to 2400 °C does not exceed 1.2 × 1019 cm−3 at growth on the 〈0001〉 plane of substrate, but is lower at growth on the 〈0001〉 plane and in the mentioned temperature range the solubility changes from 2 × 1018 to 7 × 1018 cm−3. Data obtained cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Gallium is another acceptor impurity in silicon carbide, but with a lower solubility than Al (~1.2-10 19 cnT 3 ) 53 ' 21 and a higher ionization energy [£ v +0.29eV (6H) and £ v +0.3eV {AH)] 53 ' 54 , which is commonly not used for fabrication of p-n structures. Some authors have observed two acceptor levels (E v +0.31 and E v +0.37 eV) related to Ga in 6H-S1C 5S .…”
Section: Galliummentioning
confidence: 99%
“…Gallium is another acceptor impurity in silicon carbide, but with a lower solubility than Al (~1.2-10 19 cnT 3 ) 53 ' 21 and a higher ionization energy [£ v +0.29eV (6H) and £ v +0.3eV {AH)] 53 ' 54 , which is commonly not used for fabrication of p-n structures. Some authors have observed two acceptor levels (E v +0.31 and E v +0.37 eV) related to Ga in 6H-S1C 5S .…”
Section: Galliummentioning
confidence: 99%
“…Irradiation of other SiC polytypes gave rise to luminescence with similar properties [52]. Since this luminescence emerged as a result of irradiation or implantation of SiC with various ions, it was assumed that a center acting as the activator of luminescence had either a pure defect-related structure or was a complex which consisted of an intrinsic defect and an atom of a background impurity [58][59][60]. Choyke [61] detected excitons bound to deep-level centers in SiC.…”
Section: Defect-related Luminescencementioning
confidence: 99%
“…the D I defect is very stable. The D I center was observed in all polytypes after various kinds of irradiation [1,[3][4][5][6], and was also observed in as-grown material after quenching from growth temperature and in epitaxial layers grown by chemical vapor deposition (CVD) [7][8][9][10] or molecular beam epitaxy (MBE) [11]. The photon energy of the zero-phonon luminescence is 0.35-0:45 eV below the excitonic gap independent of the polytype.…”
Section: Introductionmentioning
confidence: 96%